Statistical study of the foreign exchange market environment - V. N. Saline; O. Yu. Sitnikova; M. V. Vakhrameeva (Статистика и экономика)
The authors attempted to conduct a statistical study of foreign exchange market and its environment, determined the theoretical basis of the study and aspects of practical application of the obtained results. To achieve this goal, the authors defined the subject of the statistical study of the foreign exchange market environment, structured scorecard to assess the state of the foreign exchange market, indicated the sources of information for the statistical analysis of the foreign exchange market environment in various areas. In the process of writing the article, the authors also used relevant materials on the topic of the research developed and published by the authorized organizations, including the international ones. In the study of the currency market and its situation in various areas the authors identified its importance for the financial stability of the national economy, the relationship with other segments of the fi nancial market, and the impact on macroeconomic indicators of economic development. Special attention was paid to the system of indicators to characterize the currency market environment, which is the methodological basis of the study and analysis of phenomena and processes occurring in the foreign exchange market. The authors compiled and structured a system of statistical indicators for the analysis of the status and development of the currency market in various areas in accordance with the available sources of information. This article discusses the issues related to deriving statistical data about the currency market from offi cial and alternative sources, the assessment of the completeness and reliability of statistical information was conducted, directions to improve statistical monitoring of the foreign exchange segment of the fi nancial market were determined. In the article, considerable attention is paid to the methodology of calculating separate indicators, including derivatives, in accordance with national and international statistical standards. In the study the authors came to the conclusion that currently, primary foreign exchange statistical information is suffi cient for calculating the recommended indicators characterizing the foreign exchange market environment, including supply and demand, and their correlation. In addition, the Bank of Russia has enough statistics to study the current situation with the sources of currency supply and demand in a relatively longer term. The indicators of the currencies turnover, its detailed structure, currency exchange rates, their fluctuations, and the business activity indicators are calculated fully or have the necessary reliable information for their assessment.